Modeling the Intermittent Lava Lake Drops Occurring Between 2015 and 2021 at Nyiragongo Volcano. Issue 8 (12th April 2023) - Walwer, D.; Wauthier, C.; Barrière, J.; Smittarello, D.; Smets, B.; d'Oreye, N.
Abstract: Between 2015 and 2021, Nyiragongo's lava lake level experienced a linear increase punctuated by fast intermittent drops. These drops occurred synchronously to seismic swarm at approximately 15 km below the surface and extending laterally NE from the volcano. To interpret these lava lake level patterns in terms of reservoirs pressure evolution within Nyiragongo, we consider the following simplified plumbing system: a central reservoir is fed by a constant flux of magma, distributing the fluid up into the lava lake and laterally into a distal storage zone. Magma transport is driven by a pressure gradient between the magma storage bodies, accommodating influx and outflow of magma elastically, and the lava lake. Lateral transport at depth occurs through a hydraulic connection for which the flow resistance is coupled to the magma flux. When the right conditions are met, lateral magma transport occurs intermittently and triggers intermittent lava lake level drops matching the observations. Plain Language Summary: The level of lava lakes fluctuates in response to magma motion in the underlying crust. Prior to the May 2021 flank eruption, Nyiragongo's lava lake level displayed a series of rapid drops in concert with ∼15 km deep earthquakes likely caused by crustal magma movements deforming and fracturing the surrounding rocks. The present work studies the simplified physics of magma motion at depth draining the lava lake. We show that a valve‐like mechanism either preventing or enabling deep magma flow can cause successive lava lake level drops as observed between 2015 and 2021 at Nyiragongo. Key Points: Nyiragongo 2015–2021 successive lava lake level drops modeled as the result of ∼15 km deep lateral transport of magma Nyiragongo's modeled central reservoir distributes the fluid up into the lava lake and laterally into a distal storage zone Lava lake overflows exert top‐down control on magma transport phenomena occurring in the deeper part of the plumbing system